Western Australian Peritonectomy Service: a review of the first 6 years of operation of a low‐volume peritonectomy centre. Issue 5 (15th February 2021) - McEntee, Phillip; Keelan, Simon; Salama, Paul; Moroz, Paul
Abstract: Background: Cytoreductive surgery (CRS) with hyperthermic intraperitoneal early chemotherapy has gained acceptance as the standard of care for peritoneal surface malignancy over the past decade. This study reports the results of the first 6 years of activity of the Western Australian Peritonectomy Service to compare outcomes of a low‐volume centre with world standards. Methods: An audit of all patients who received CRS ± hyperthermic intraperitoneal early chemotherapy treatment at the Western Australian Peritonectomy Service in its first 6 years of operation was performed and results were compared to the recent world literature. Results: A total of 130 patients were treated with 150 CRS procedures, including 50 pseudomyxoma peritonei (PMP), 53 colorectal cancers (CRCs), 27 appendix adenocarcinomas (AAs) and 20 other cancers. The median operating time was 12 h with median length of hospital stay of 15 days. Perioperative mortality was 0.67% and Clavien‐Dindo III/IV morbidity was 20%. The mean packed red cell transfusion requirement was 0.34 units/case. Post‐discharge readmission rate was 25% and the return to theatre rate was 13%. The 4‐year overall survival rates for PMP, CRC and AA were 97%, 49% and 81%, respectively. The 3‐year disease‐free survival rates for PMP, CRC and AA were 74%, 26% and 36%, respectively. Conclusion: A CRS centre averaging 25 cases per year can achieve strong outcomes in line with high‐volume world centres. Abstract : This study reviews the results of the first 6 years of activity of the Western Australian Peritonectomy Service. It shows strong outcomes with respect to survival and morbidity, demonstrating that a low‐volume peritonectomy centre can achieve results comparable with higher volume world centres and so fill an important niche within a state's oncology service.